Foreword - Navickienė, Aušra (Knygotyra, 2023)
-To recognise the exceptional role of the first Eastern European printer Francysk Skaryna in the culture of the Grand Duchy of Lithuania, intercultural relations, the pro-European society of the neighbouring Belarusian society, and the development of Lithuanian statehood, the Seimas of the Republic of Lithuania proclaimed the year 2022 as the Year of Francysk Skaryna. The most important scientific event of the year was the international scientific conference initiated by the Department of Book, Media and Publishing Studies of the Faculty of Communication of Vilnius University and the Wroblewski Library of the Lithuanian Academy of Sciences and entitled Francysk Skaryna and the Renaissance Book Culture: Skaryna’s Little Traveller’s Book Turns 500 which took place on 22–23 September 2022. In collaboration with foreign and Lithuanian partners – the global Society for the History of Authorship, Reading and Publishing (SHARP), the Charles University in Prague, the Institute of the Lithuanian Language, the Institute of Lithuanian Literature and Folklore, and the Lithuanian Academy of Sciences – the organisers succeeded in bringing together researchers from fifteen European and North American countries representing a variety of academic schools. In order to cover such a wide field of interdisciplinary research, the conference was attended by world-class experts in Renaissance book culture and scholars of Skaryna as the guest speakers: Dr. Alexandra Gillespie from the University of Toronto Mississauga, Prof. Dr. James Raven from the Universities of Essex, Cambridge and Trondheim, Habil. Dr. Alexander Grusha, Associate Professor Habil. Dr. Ilya Lemeshkin from the Charles University in Prague, and Habil. Dr. Sergey Temchin from the Institute of Lithuanian Language. During the two days, in eight sessions, scholars of communication and information, and researchers of ancient literature, language and history addressed questions concerning prominent figures of Renaissance printing culture and the phenomena of the creation, publishing, production, dissemination and reception of print media, the first post-incunabula of the Grand Duchy of Lithuania, the culture of the manuscript book in the Grand Duchy and other European regions, the spread of printing in Europe, and the special features of print media culture in the Grand Duchy, institutional and private libraries, reading and readers, the dissemination of books in society, and the manuscript and printed heritage of the Grand Duchy and its communication.In response to the invitation, distinguished guests and sponsors participated in the opening of the conference. The conference participants were greeted by Head of the Government of the Republic of Lithuania, Prime Minister Ingrida Šimonytė, the President of the Lithuanian Academy of Sciences, Academician Prof. Habil. Dr. Juras Banys, the Rector of Vilnius University, Prof. Dr. Rimvydas Petrauskas, the President of the Society for the History of Authorship, Reading and Publishing, the world’s leading organisation in such scholarship, Assoc. Prof. Dr. Shef Rogers from the University of Otago in New Zealand (the fifth president of SHARP who continues his cooperation with the organisers of the Vilnius Book Studies Conferences), and Dr. Małgorzata Stafanowicz-Pecela, Director of the Polish Institute in Vilnius and Counsellor of the Embassy of the Republic of Poland in Vilnius.This anniversary-related scientific event continued the tradition of interdisciplinary conferences on book studies in Vilnius. It became the nineteenth international conference initiated by book scholars of Vilnius University and the third conference in Vilnius organised in cooperation with SHARP. It was also the first academic event to gain the status of a Vilnius Municipality-sponsored event. The hybrid mode of the conference delivery, simultaneous translation, and the rich social programme of the event helped the organisers reach a wide multilingual audience of participants and create an environment conducive to informal scholarly communication, which is important for networking, planning collaborations, and sharing research ideas.This 80th volume of Knygotyra (Book Science), the international academic journal of Vilnius University, is thematic. It publishes scholarly articles on Skaryna studies and Renaissance book culture developed by the authors on the basis of their conference presentations. It also publishes materials relating to the discussion about the time and place of the printing of Skaryna’s Little Traveller’s Book (Malaya podorozhnaya knizhica) which took place during the conference. We hope that this volume will serve as a means of introducing international scholarly audiences to the latest insights of Skaryna studies and scholars of Renaissance book culture from different schools of thought, the achievements of international research in the culture of the Grand Duchy of Lithuania, and the approach to Skaryna’s publishing as a European and humanist activity and as a phenomenon of Renaissance European book culture.